Verbesserte Qualität gelagerter Erythrozytenkonzentrate durch maschinelle Autotransfusion - Münch, Frank; Purbojo, Ariawan; Wenzel, F.; Kohl, M.; Dittrich, Sven; Rauh, Manfred; Zimmermann, Rüdiger; Kwapil, Nicola (Die Anaesthesiologie, 2022)
Background The transfusion of packed red blood cells (PRBC) is associated with various side effects, including storage damage to PRBCs. The cells change their structure, releasing potassium as well as lactate. Mechanical rinsing, available in many hospitals, is able to remove toxic substances and possibly minimizes the negative side effects of transfusion. Objective The primary aim of our study was to improve the quality of PRBCs before transfusion. The effects of different washing solutions on PRBC quality were analyzed. Material and methods This in vitro study compares 30 mechanically washed PRBCs. They were either processed with standard normal saline 0.9% (n = 15, N group) or a hemofiltration solution containing 4 mmol/l potassium (n = 15, HF group) by a mechanical rinsing device (Xtra, LivaNova, Munich, Germany). A subgroup analysis was performed based on the storage duration of the processed PRBCs (7, 14, 37 days). Samples were taken before washing (EKpra), immediately after washing (EKpost) and 10 h later (EKpost10h), after storage in the "wash medium" at room temperature. Concentrations of ATP (probability of survival in transfused erythrocytes), lactate, citrate and electrolytes (potassium, sodium, chloride, calcium) were tested. Results and conclusion Mechanical rinsing improves pretransfusion quality of PRBC. Washing with a hemofiltration solution results in a more physiological electrolyte composition. Even 10 h after mechanical rinsing with a hemofiltration solution, the quality of 37-day-old PRBC is comparable to young PRBC that have been stored for 7 days and have not been washed. Washing stored PRBC increases the ATP content, which subsequently leads to an increased probability of survival of red cells after transfusion.
CRIS-Team WoS Importer:2022-08-26